2013
DOI: 10.3164/jcbn.12-96
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of polysaccharides from Boschniakia rossica on carbon tetrachloride-induced toxicity in mice

Abstract: The purpose of this study was to investigate the protective effect of polysaccharides from Boschniakia rossica against hepatotoxicity induced by carbon tetrachloride (CCl4). Boschniakia rossica polysaccharides was administered intragastrically once daily for 7 days. One hour after the final treatment, mice were treated intraperitoneally with 80 mg/kg of CCl4. CCl4-induced hepatotoxicity was manifested by increased levels of serum marker enzymes and hepatic lipid peroxidation, and by decreased potential of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The preparation of BRP was performed as previously described with a minor modification. ( 22 , 26 , 28 ) Briefly, the water-soluble crude polysaccharides were obtained from Boschniakia rossica by defatting with ethanol, hot water extraction, ethanol precipitation, deproteinization by Sevag method and repeated unfreezing process, dialysis against water and lyophilization. The yield of crude polysaccharide accounted for 3.3% of the whole plant.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The preparation of BRP was performed as previously described with a minor modification. ( 22 , 26 , 28 ) Briefly, the water-soluble crude polysaccharides were obtained from Boschniakia rossica by defatting with ethanol, hot water extraction, ethanol precipitation, deproteinization by Sevag method and repeated unfreezing process, dialysis against water and lyophilization. The yield of crude polysaccharide accounted for 3.3% of the whole plant.…”
Section: Methodsmentioning
confidence: 99%
“…( 18 23 ) In recent decades, polysaccharides isolated from botanical sources (mushrooms, algae, lichens and higher plants) have attracted a great deal of attention in the biomedical arena because of their relatively low toxicity and various biological properties. ( 22 26 ) Polysaccharides from Boschniakia rossica had been reported to have anti-oxidative and anti-inflammatory functions, and have characteristics of non-toxicity. ( 22 , 23 , 25 , 26 ) Furthermore, our previous experiment showed that oral administration of Boschniakia rossica polysaccharides play a protective role in CCl 4 -induced acute liver injury by inhibiting lipid peroxidation and suppressing inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations